A mezőgazdasági foglalkoztatottság regionális jellemzői - Karácsony, Péter (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Employment in agricultural services has always been affected by politics, by technical development etc. These facts caused more and more people rapidly lose their jobs in agri-cultural services within the last several years. Due to the above mentioned affects, two-third of the people working with agriculture was forced to give up their jobs. Many people lost their jobs in the country which caused deep social problems (fewer inhabitants in villages). During my researches, I evaluated at the agricultural employment rates in Hungary.